Mood and well‐being of novice open water swimmers and controls during an introductory outdoor swimming programme: A feasibility study. Issue 2 (10th November 2020) - Massey, Heather; Kandala, Ngianga; Davis, Candice; Harper, Mark; Gorczynski, Paul; Denton, Hannah
Abstract: Background: Anecdotal evidence suggests that outdoor swimming can improve mood. This feasibility study examined the mood and well‐being in participants attending an outdoor swimming course. Methods: Profile of Mood States and Short Warwick–Edinburgh Mental Well‐being Scale questionnaires were completed by participants on a 10‐week introductory outdoor swimming course (61 swimmers) and 22 controls who sat on the beach. Questionnaires were completed before and after three sessions: the first session (pool based), their first outdoor swim (session 4) and their final outdoor swim (session 10). Results: Swimmers reported acute increases in positive subscales (Esteem and Vigour, P  < .001) and reductions in negative subscales (Tension, Anger, Depression, and Confusion and Total Mood Disturbance [TMD], P  < .001, d  = 1.1–1.7). TMD was also reduced between sessions ( P  < .001, d  = 0.08). Well‐being also increased during the course in swimmers ( P  < .001, d  = 3.7) and controls ( P  = .019, d  = 0.2). Greater reductions in TMD ( P  < .001, d  = 0.8–2.5) and increases in well‐being were observed in swimmers than controls ( P  = .034, r  = .23). Conclusions: Novice outdoor swimmers participating in a 10‐week introductory outdoor swimming course had acute and chronic reductions in negative mood, increases in well‐being and acute increases in positive mood. Controls mood scores fluctuated and were similar at the start and end of the course, whereas well‐being scores improved by the final session. Tension scores peaked in both swimmers and controls immediately before the first outdoor swim. Nonetheless the swimmers' improvement in mood and well‐being scores was significantly greater than that of the controls. The nature of the study does not provide mechanistic understanding; there are likely to be a number of explanations (physiological, psychological and sociological) for the changes in mood and well‐being in swimmers and controls that can be investigated further.